Motivasi Australia Memberikan Bantuan Luar Negeri kepada Indonesia dalam Menangani Penyebaran COVID-19 Tahun 2020-2021 - Ilham Agustian Candra; Arie Kusuma Paksi (Universitas Muhammadiyah Sorong, 2021)
This research focused to discuss the motivation behind Australiaâ€™s foreign aid to Indonesia in order to tackle the transmission of COVID-19 in 2020-2021. According to data, the case of COVID-19 spreading in Indonesia has escalated continuously. Hence, Australia is concerned about providing foreign aid to Indonesia. The conceptual framework that was used in this article is the concept of national interest. The qualitative methods and descriptive analysis approach were also used in this research. Through library resources with collecting the data sourced from books, documents, journals, and electronic sources that the validity can be accounted for, this article explained that Australia as a country providing aid to Indonesia places interest in the health sector and the private sector. Furthermore, the result of this research concludes that the aid provided by Australia to Indonesia is an intention to defend Australiaâ€™s national interests related tohealth research while strengthening the economic sector obtained from the results of cooperation amid the COVID-19.Â